Printing cancer cells into intact microvascular networks: a model for investigating cancer cell dynamics during angiogenesis. Issue 9 (1st September 2015) - Phamduy, Theresa B.; Sweat, Richard S.; Azimi, Mohammad S.; Burow, Matthew E.; Murfee, Walter L.; Chrisey, Douglas B.
<x xml:space="preserve">Abstract</x> A novel ex vivo model combining cell printing and tissue culture to investigate cancer cell dynamics during angiogenesis in intact microvascular networks.